Functional analyses of a novel missense and other mutations of the vitamin D receptor in association with alopecia - Mayuko Tamura (Nature Portfolio, 2017)
Abstract Hereditary 1,25-dihydroxyvitamin D-resistant rickets (HVDRR) is a rare disorder, caused by bialellic mutations of the vitamin D receptor (VDR) gene, sometimes associated with alopecia. The aim of this study is to elucidate the mechanism of functional disruption of a novel mutation, detected in a patient with HVDRR, comparing to other mutations with or without alopecia. The patient was a 2-year-old girl with alopecia, who was clinically diagnosed as HVDRR. Genetic analysis revealed a novel homozygous mutation, S360P, located in ligand binding domain (LBD). The mutation was predicted as not disease causing by Polyphen2 and SIFT. But the transcriptional activity of S360P was disrupted as well as other reported mutations, Q152X (located in the hinge lesion), and R274L, H305Q (located in LBD). Following assays revealed no ligand binding affinity, no interaction with cofactors or RXR and no functioning of nuclear localization signals. Our results provide an additional evidence for the previous findings suggesting that DNA binding by the VDR/RXR heterodimer is essential for the function of the VDR in hair development. In conclusion, we identified a novel missense mutation of VDR causing HVDRR with alopecia. Functional analyses revealed that the single amino acid substitution could disrupt the function of the protein.